Cervical Distraction‐Stabilization Using an Intervertebral Spacer Screw and String‐of Pearl (SOP™) Plates in 16 Dogs With Disc‐Associated Wobbler Syndrome. Issue 5 (1st May 2015) - Solano, Miguel A.; Fitzpatrick, Noel; Bertran, Judith
Abstract : Objective: To retrospectively investigate a novel surgical technique using the Fitz Intervertebral Traction Screw (FITS) combined with string‐of‐pearl (SOP™) locking plates for the treatment of Disc Associated Wobbler Syndrome (DAWS). Study design: Case series (n = 16). Methods: Ventral approach and fenestration of the affected disc(s), nuclear extirpation, and insertion of the FITS device to the level of the dorsal annulus was followed by application of one or two 3.5 mm SOP™ plates. Autogenous cancellous bone graft was placed between adjacent vertebrae. Long‐term followup (>12months) via telephone or examination was attempted for all dogs. Results: Case records of 16 dogs were reviewed. All dogs had Type II disc disease with a single site in 13 dogs and multiple sites in 3 dogs. Mean ± SD age was 75 ± 38 months and body weight was 34 ± 7 kg. Fifteen of the 16 dogs had significantly improved neurologic status ( P =.01) at 6 weeks. Seven of the 16 dogs were examined at 24–36 months with 6 considered normal and 1 had mild ataxia. Postoperative radiographic intervertebral distraction was significant ( P = .01). Radiographic bridging was recorded in 10/16 dogs at 6 weeks and in 7 dogs available for follow‐up at 5–36 months. Computed tomography in 3 dogs at 24–36 months and postmortem with histology in 1 dog confirmed bone‐bridging. Complications were not considered clinically significant and included implant loosening (2 dogs, both single plates) and minor end‐plate subsidence (8 dogs). Conclusion: Application of the FITS device in combination with 2 ventral SOP™ locking plates and autogenous cancellous bone graft was associated with excellent outcomes in dogs treated for DAWS in this small case series.